Cytotoxicity Evaluation of Iranian Propolis and Calcium Hydroxide on Dental Pulp Fibroblasts - Maryam Zare Jahromi; Parisa Ranjbarian; Samaneh Shiravi (Tabriz University of Medical Sciences, 2014)
Background and aims. Since intracanal medicaments can affect the cell viability in periapical tissues, the aim of this study was to evaluate the effect of calcium hydroxide and propolis on pulp fibroblasts. Materials and methods. Two healthy third molars were used as a source to obtain fibroblasts. The fibroblasts were cultured and subjected to 1 mg/mL of propolis and calcium hydroxide. This experiment was performed in six replicates and cell viability was evaluated with MTT assay. Statistical analysis was performed by t-test. Results. Comparison of cell viability with the use of 1 mg/mL of calcium hydroxide and propolis showed that cells sub-jected to propolis were more viable when compared to calcium hydroxide (P < 0.05). Conclusion. In this study, calcium hydroxide reduced fibroblast viability, significantly more than Iranian propolis. Other properties should be evaluated before Iranian propolis could be indicated for use as intracanal medicament.